Implementing Distributed Shared Memory for Dynamic Networks. - MUSIAL, PETER; NICOLAOU, NICOLAS; SHVARTSMAN, ALEXANDER A. (Communications of the ACM, 2014)
The article discusses the storage of shared readable and writable data in distributed systems with emphasis on implementations that offer resiliency and consistency in dynamic settings. Topics discussed include the storage system providing seamless runtime migration of data whether the concern is data longevity or mobility, a general distributed setting for establishing consistent shared-memory services, and the need for algorithms made for static settings to accommodate some dynamic behaviors like asynchrony, transient failures, and permanent crashes within certain limits.